Effective transfer of safety interventions within and between organizations: Leveraging translation theory to achieve improved outcomes - Pilbeam, Colin; Karanikas, Nektarios (Elsevier, 2023)
Safety interventions are often ‘borrowed’ from one organizational setting, where they have worked successfully, to another organizational setting but not necessarily with the same positive outcomes. Translation theory could offer potential insights into the processes through which managers translate safety practices either from one organization to another or from one part to another part of the same organization. To examine this possibility, this study used the framework method of analysis, underpinned by a conceptual framework developed from translation theory, to analyse qualitative data from interviews with experienced managers having responsibility for safety in their organization who shared narratives of eight different safety interventions deployed in a variety of industry sectors ranging from oil and gas to retail from around the world. By inference from the data, analysis shows that interventions of low complexity, low embeddedness and high explicitness which theory characterises as more translatable, were also in practice more successfully translated. Furthermore, interventions with senior management support had higher levels of interpretive viability, thus making them more transformable and ensuring translation success. Also, translations were more successful when the safety interventions received adequate resourcing, were targeted at a narrow rather than a broad organizational scope and where they were integrated into existing work practices. The conceptual elements of the framework adopted in this study have the potential to support the development of translation competence among safety professionals, thus permitting the future deployment of more effective safety interventions in the workplace to reduce accidents and injuries.
Keywords: Context; translation competence; transformability; translatability; safety interventions